FEATURES OF THE COURSE OF RHEUMATOID ARTHRITIS DEPENDING ON THE POLYMORPHISM T-786C GENE OF ENDOTHELIAL NITRIC OXIDE SYNTHASE - Букач, О.П.; Федів, О.І.; Сидорчук, Л.П. (World of Medicine and Biology, 2016)
Тo assess polymorphic variants of eNOS gene (rs 2070744) in patients with RA depending on the degree of activity of acute-phase indicators. Material and methods. During the study involved 60 patients with RA who gave written informed consent to participate in the study and 20 healthy individuals representative by age and sex. Molecular genetic study of the polymorphism of T-786C gene еNOS conducted in a public institution "Reference center" The Ministry of health Ukraine (Kiev) by polymerase chain reaction (PCR). Results. We have analyzed the influence of the polymorphism T-786C in the promoter of the gene of endothelial nitric oxide synthase (eNOS) on the course of rheumatoid arthritis (RA), which was accompanied by an increase in blood of acute-phase indices of inflammation, joint disorders, connective tissue 1.67-102,28 times (p≤0,049-0,001), which, however, has no clear dependence on polymorphic variants of eNOS gene (rs 2070744), except for C-reactive protein, which is higher in carriers of the unfavorable СС-genotype by 32.13% (p=0,035). Also among homozygous carriers of the mutant C-allele are relatively more common entity with the content of IgG antibodies to cyclic citrullinemia peptide (A-CCP) in blood plasma higher than normal values" by 18.29% (p=0.04), with more severe RA (III degree of activity) – 14.28% (p=0.001) and high level functional failure of the joints (3 degree) by 22.12%. According to epidemiological risk analysis favorable TT genotype associated with lower activity of RA (I stage ) [OR=0,21; p=0.007], lower radiographic stage (I stage) and to a lesser extent to functional failure of the joints (I stage) [OR=0,10; p=0,021].